Besigheidsprosesbestuur in mensetaal-tegnologiehulpbronontwikkeling:'n gevallestudie. - Janke, U. (Literator, 2008)
Resources play a crucial role in human language technology (HLT), since research and development are largely dependent on its availability. It follows that effective management of these resources is essential to this domain and there are a number of international initiatives that contribute towards such management, e.g. through setting standards for development. Against this backdrop, the objective of this particular article is to investigate the potential of business process management (BPM) to facilitate effective management and standardisation of HLT resource development. BPM systems and principles are commonly applied in production, revenue cycles, process documentation, risk and project management, and a variety of other administrative areas, to improve efficiency. However, its application in the context of HLT resource development has not been thoroughly investigated in the literature. This article presents a theoretical BPM framework for standardisation which takes cognisance not only of routine processes, but also of the unique nature of HLT when it entails software development, which is marked by creative problem-solving processes that are difficult to control. The framework is composed of philosophy and culture definition, standardisation along a selected framework, protocols and tools, and deployment. The validity of this framework is tested in a case study of an HLT research and development centre. Preliminary findings suggest that the framework has the potential to standardise HLT resource development and management processes.